Intradiaphragmatic abscesses in a wild boar (Sus scrofa): Inspective implications based on anatomopathological evidences - Andrea Piccinini; Gianluigi Ferri; Alberto Olivastri; Fabio Rossi; Anna Rita Festino; Alberto Vergara (Italian Journal of Food Safety, 2022)
The intradiaphragmatic localization of an abscess is rarely described in humans and in other animal domestic and wild species, and can be caused by penetrative traumas (i.e., firearm injuries). Here we describe two intradiaphragmatic abscesses in a hunted adult male wild boar (Sus scrofa) pluck, associated with adhesion phenomena with the contiguous anatomical structures (pleural, phrenic, and glissonian serosas) and observed during the post mortem inspection, in accordance with the Reg. EU 627/2019. One of these lesions also presented a phreno-abdominal fistula. We found in cytopathological evaluation of the neoformations’ content the presence of spheroidal bacterial soma, characterized by linearly concatenated “Streptococcus-like” aggregation pattern. Furthermore, microbiological assays revealed a polymicrobial pattern characterized by the presence of telluric microorganisms, some of which have a marked pyogenic action (Streptococcus suis type I, Sphingomonas paucimobilis, Carnobacterium divergens, and Lactobacillus sakei). Our results and collected evidence demonstrate the pathogenetic hypothesis of bacterial contamination secondary to penetrative trauma caused by a not-mortal projectile’s wound, defining the inspective behaviour according to the cogent legislation. These lesions, in the reason of their potential relation to toxemia, bacteremia and septicemia phenomena, represent a sanitary risk that impose, from a normative point of view, the total condemnation of the carcass. These inspective implications, originating from the observation and interdisciplinary description of the anatomopathological and microbiological features of the lesions, are directly projected on the normative scenario, providing useful elements to guarantee the health of the consumer.